“I Can Definitely Find Ways to Entertain Myself. Like Listening to Music, I Listen to a Lot of Music”: Children’s Musical Assemblages During COVID-19 - Donison, Laurel; Raby, Rebecca (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2023)
This paper explores children’s engagements with music during the beginning of the COVID-19 pandemic in Canada. We draw on repeated, qualitative, online interviews with children that explored their experiences during the pandemic. During these interviews, the topic of music came up many times and was present in the children’s lives in many ways. Inspired by Christopher Small’s concept of musicking to understand music as an action, and grounded in new-materialist emphasis on the interweaving of human and nonhuman entities, we examine children’s musical assemblages to discuss how they engaged with music to express themselves and connect to others early in the pandemic in ways that helped them through a difficult time.